Neoutopismo no antropoceno: agenciamentos coletivos e micropolíticas de resistência no Rio Grande do Sul, Brasil - Hübner, Jeniffer (2016)
It is intended to reflect, from the perspective of the micropolitics of resistance proposed by Félix Guattari, on the updates that we can give to the term utopian in contemporary times based on the analysis of collective agencies and community living, seeking to understand how the production of subjectivities and narratives respond to the crisis of the Anthropocene. I question: to what extent can contemporary collective agencies and community living be considered utopian? What updates can we give to the term utopian based on the experiences of the researched communities and subjects? For this, I undertook research in four territories located in the municipality of Maquiné in Rio Grande do Sul, Junana, Pé do Arco Íris, Aterra and AMÓ, to understand to what extent they can be considered as utopian. Above all, I sought to trace differences and similarities between the experiences prior to the crisis of utopias at the end of the 20th century and the current ones. In the methodological path, with an ethnographic approach, various techniques were used, such as participant observation and semi-structured interviews. The notion of neo-utopianism proposes to reflect on how the sense of utopia is updated after the crisis of utopias and in the context of the Anthropocene, linking it to the proliferation of minority becomings and collective agencies that act in the face of the fight against climate change and anti-destruction of the human biosphere. I understand that practices in a utopian sense are currently produced in territorialized spaces that seek to carry out other possible ways of inhabiting the world, less harmful to biodiversity and consequently to human life, for that, they resort to collective agencies, community experiences and sustainable practices, and therefore, configuring new territorialities, temporalities and singularizations that establish lines of flight in the context of contemporary capitalism. Practices with a utopian meaning are located in the sensitive, everyday, perceptive dimension, but, above all, refer to the creation of resistance possibilities amidst the post-pandemic scenario of deepening socio-environmental inequalities and conflicts.